Influence of Virus Strain on the Efficacy of Vaccine Against Avian Influenza Virus Subtype H7N3 - Sattar, S.; Naeem, K.; Ahmed, Z.; Malik, S.A. (International Journal of Poultry Science, 2007)
To evaluate the effect of in ovo passaging on the biological activity and immunogenicity of various H7N3 Avian Influenza Virus (AIV) isolates, three field H7N3 isolates (A/Chicken/Pakistan/Murree/NARC/69/04 (H7N3); A/Chicken/Pakistan/Rawalpindi/NARC/160/04 (H7N3); A/Chicken/Mansehra/NARC-214/04 (H7N3)) from the outbreak of 2003-04 were propagated in ovo up to 30th passage. After each 10 passages, the isolates were inactivated, injected into 10 days old chicks subcutaneously and seroconversion monitored by Haemagglutination Inhibition (HI) test. The vaccinated chicks were then challenged with the corresponding virus isolate and the mortality and virus shedding was recorded post-challenge. The results showed that the isolate A/Chicken/Murree/NARC-69/04 (H7N3) was relatively more immunogenic since the vaccinated chicks produced the highest HI antibody titers than the chicks inoculated with the other two strains of H7N3 AIV. The virus shedding upon challenge was also lowest in chickens in this group. On the contrary, the isolate A/Chicken/Mansehra/NARC-214/04 (H7N3) was less immunogenic despite repeated passaging up to 20th passage, however, the antibody titers did increase after 30th passage. The virus recovery from organs was minimal in group given vaccine prepared from Murree isolate and highest for Mansehra isolate. No mortality was observed in any of the vaccinated and challenged group of any combination in this study. This study therefore identified the Murree isolate (A/Chicken/Pakistan/Murree/NARC/69/04) as a better candidate for vaccine preparation among the currently circulating H7N3 isolates in Pakistan. The results of this study imply that a careful assessment of the vaccine potential of an isolate must be made in meeting defined vaccine strain criteria before including that isolate in vaccine production chain.